2018
DOI: 10.1371/journal.pone.0189710
|View full text |Cite
|
Sign up to set email alerts
|

AMYCNE: Confident copy number assessment using whole genome sequencing data

Abstract: Copy number variations (CNVs) within the human genome have been linked to a diversity of inherited diseases and phenotypic traits. The currently used methodology to measure copy numbers has limited resolution and/or precision, especially for regions with more than 4 copies. Whole genome sequencing (WGS) offers an alternative data source to allow for the detection and characterization of the copy number across different genomic regions in a single experiment. A plethora of tools have been developed to utilize W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…This is in contrast with data from Falchi and colleagues and other studies using qPCR that showed an approximate normal distribution of AMY1 copy number [10,13,22,25]. Furthermore, the copy numbers of AMY1 and AMY2A were shown to be significantly correlated in European populations by two studies using accurate CNV measurement techniques: the first used PRTs and microsatellite measurements [46], while the second used a novel method, 'automatic modeling functionality for copy number estimation', or 'AMYCNE', which uses whole genome sequencing data and appears to exhibit a similar level of accuracy to ddPCR [57]. The haplotype arrangements of AMY1 and AMY2A CNV are also correlated.…”
Section: Association Between Cnv Within Amy1 and Bmimentioning
confidence: 99%
“…This is in contrast with data from Falchi and colleagues and other studies using qPCR that showed an approximate normal distribution of AMY1 copy number [10,13,22,25]. Furthermore, the copy numbers of AMY1 and AMY2A were shown to be significantly correlated in European populations by two studies using accurate CNV measurement techniques: the first used PRTs and microsatellite measurements [46], while the second used a novel method, 'automatic modeling functionality for copy number estimation', or 'AMYCNE', which uses whole genome sequencing data and appears to exhibit a similar level of accuracy to ddPCR [57]. The haplotype arrangements of AMY1 and AMY2A CNV are also correlated.…”
Section: Association Between Cnv Within Amy1 and Bmimentioning
confidence: 99%
“…S6a). Using this simulated data, we benchmarked the performance of CNAtra against five RD-based single-sample CNV detection tools which include ReadDepth [14], CNVnator [9], FREEC [10], CLImAT [16] and AMYCNE [11]. We analyzed the performance of these tools after optimizing their parameters for low-coverage data (see Extended Methods under Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…S8a). Using this simulated data, we benchmarked the performance of CNAtra against five RD-based single-sample copy number detection tools which include ReadDepth [20], CNVnator [15], FREEC [16], CLImAT [22] and AMYCNE [17]. We analyzed the performance of these tools after optimizing their parameters for low-coverage data (see Extended Methods under Supplementary Information).…”
Section: Cnatra Is a Superior Tool For Detecting Large-scale And Focamentioning
confidence: 99%
“…Several tools have been presented over the years that utilize a single sequencing sample for copy number detection [15][16][17][18][19][20][21][22]. They are built on different assumptions of the underlying probabilistic distribution and percentage of chromosomal abnormalities.…”
mentioning
confidence: 99%